2015
DOI: 10.3989/gya.0233151
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and fatty acid composition of milk fat from Saudi Aradi goat

Abstract: SUMMARY:Goat milk is the second most prevalent edible milk in Saudi Arabia and is one of the most prominently produced milks in the world. Few studies have focused on the physicochemical properties of goat milk fat (GMF). Samples of Saudi Aradi goat milk were obtained during the spring dairy season to determine the physicochemical characteristics and fatty acid composition of the GMF. The physicochemical properties of Saudi Aradi GMF were as follows: iodine value, 23.2 g of I 2 ·100 g −1 of fat; saponification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…The profiles of the TG and DTG curves in oxygen showed five stages of decomposition of milk fat, with maximum temperature at 95, 296, 340, 414, and 511°C. Sbihi et al [31] obtained similar results by studying goat milk fat under dry air atmosphere. Milk fat due to its structure is polymorphic fat [32].…”
Section: Resultsmentioning
confidence: 63%
“…The profiles of the TG and DTG curves in oxygen showed five stages of decomposition of milk fat, with maximum temperature at 95, 296, 340, 414, and 511°C. Sbihi et al [31] obtained similar results by studying goat milk fat under dry air atmosphere. Milk fat due to its structure is polymorphic fat [32].…”
Section: Resultsmentioning
confidence: 63%
“…Sbihi et al [21] investigated goat milk fat. They observed that during DSC analysis, melting curve exhibited two melting peaks at 15.4°C and 38.7°C, respectively.…”
Section: Melting Characteristic By Dscmentioning
confidence: 99%
“…In contrast to a nitrogen atmosphere, a TG diagram performed under oxygen atmosphere was characterized by four transitions; therefore, a DTG curve showed four stages of goat milk fat decomposition at maximum temperature peaks: 278.13; 409.77; 417.99; and 502.12°C. Sbihi et al [21] investigated goat milk fat by using TGA/DTG in a dry air atmosphere. The characteristic of the TGA/DTG diagrams showed three stages of decomposition for goat milk fat, with a maximum temperature at 316.5, 440 and at 541.3°C.…”
Section: Thermogravimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…These methods include gas chromatography to assay fatty acids (Molkentin and Precht, 1987;Glaeser, 2002) and triacylglycerols, which are presently determined according to the Official method (EC Regulation No. 273/2008), liquid chromatography (NogalaKałucka et al, 2008;Derewiaka et al, 2011), near infrared spectroscopy (Heussen et al, 2007), and differential scanning calorimetry, which is commonly used in studies of milk fat from various animals (Sbihi et al, 2015;Tomaszewska-Gras, 2016b). Authenticity assessment of butter is still a big challenge for analytics.…”
Section: Introductionmentioning
confidence: 99%